2014
DOI: 10.1007/s00246-014-1056-6
|View full text |Cite
|
Sign up to set email alerts
|

Balloon Dilation and Surgical Valvotomy Comparison in Non-critical Congenital Aortic Valve Stenosis

Abstract: Percutaneous balloon aortic valvoplasty (BAV) and surgical aortic valvotomy (SAV) are palliative procedures in patients with non-critical congenital valve stenosis. The aim of the study was to evaluate long-term BAV and SAV results after up to 24 years of follow-up. From 1987 to 2013, 74 consecutive interventions were performed in patients with aortic stenosis, and 62 were included in the study (39 BAVs and 23 SAVs). Age of BAV patients was 1.3 months to 17 years, and of SAV patients 1.2 months to 15 years. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 27 publications
1
27
1
Order By: Relevance
“…After operative correction of congenital heart anomalies, the most common postoperative arrhythmias are right bundle branch block, atrioventricular block second degree (Mobitz type 2), atrioventricular block grade III, left bundle branch block, paroxysmal supraventricular tachycardia, and in older children atrial fibrillation ( 9 ). The hardest dysrhythmia occur after replacing the valve, and in the postoperative valvular anomalies incidence of postoperative complete block is 60-80% with thrombosis, hypovolemia and dehydration especially in young children ( 10 ). Considering that congenital heart defects have evolving character, their early diagnosis is imperative, and complete objectification due to the complex anatomy and hemodynamics, association with other anomalies have crucial importance for the pediatric cardiac surgeon.…”
Section: Discussionmentioning
confidence: 99%
“…After operative correction of congenital heart anomalies, the most common postoperative arrhythmias are right bundle branch block, atrioventricular block second degree (Mobitz type 2), atrioventricular block grade III, left bundle branch block, paroxysmal supraventricular tachycardia, and in older children atrial fibrillation ( 9 ). The hardest dysrhythmia occur after replacing the valve, and in the postoperative valvular anomalies incidence of postoperative complete block is 60-80% with thrombosis, hypovolemia and dehydration especially in young children ( 10 ). Considering that congenital heart defects have evolving character, their early diagnosis is imperative, and complete objectification due to the complex anatomy and hemodynamics, association with other anomalies have crucial importance for the pediatric cardiac surgeon.…”
Section: Discussionmentioning
confidence: 99%
“…When multiple studies were reported from the same institution with potentially overlapping patients, the most recent study was used. After application of the inclusion/exclusion criteria, 20 studies were eligible for the meta‐analysis (Figure ) . Two database studies were included that may have overlapping patients with other single‐center reports …”
Section: Methodsmentioning
confidence: 99%
“…Both procedures were associated with low early and late mortalities. [3][4][5][6][7][8][9][10][11][12][13][14][15] With exclusion of LV hypoplasia, the overall mortality dropped to $4% at our center. Most of the early deaths had a poor clinical course with significantly dilated LV.…”
Section: Discussionmentioning
confidence: 78%